3D density model of the upper mantle of Asia based on inversion of gravity and seismic tomography data - Kaban, Mikhail K.; Stolk, Ward; El Khrepy, Sami; Al Arifi, Nassir; Beekman, Fred; Cloetingh, Sierd A. P. L.; TESAURO, MAGDALA (Geochemistry, Geophysics, Geosystems, 2016)
We construct a new-generation 3D density model of the upper mantle of Asia and its surrounding areas based on a joint interpretation of several data sets. A recent model of the crust combining nearly all available seismic data is employed to calculate the impact of the crust on the gravity anomalies and observed topography and to estimate the residual mantle anomalies and residual topography. These fields are jointly inverted to calculate the density variations in the lithosphere and upper mantle down to 325 km. As an initial approximation, we estimate density variations using a seismic tomography model. Seismic velocity variations are converted into temperatures and then to density variations based on mineral physics constraints. In the Occam-type inversion, we fit both the residual mantle gravity anomalies and residual topography by finding deviations to the initial model. The obtained corrections improve the resolution of the initial model and reflect important features of the mantle structure that are not well resolved by the seismic tomography. The most significant negative corrections of the upper mantle density, found in the Siberian and East European cratons, can be associated with depleted mantle material. The most pronounced positive density anomalies are found beneath the Tarim and South Caspian basins, Barents Sea, and Bay of Bengal. We attribute these anomalies to eclogites in the uppermost mantle, which have substantially affected the evolution of the basins. Furthermore, the obtained results provide evidence for the presence of eclogites in the oceanic subducting mantle lithosphere.